A Geographical Complementary Approach to Unveiling the Spatial Dynamics of Bradyseismic Events at the Campi Flegrei Caldera - Stefano De Falco; Claudio Martino (Geographies)
Concerning the monitoring of the resumption of seismic activity at the Campi Flegrei caldera, which is causing concern to the inhabitants and involving various protection efforts by research bodies, this work intends to constitute a complementary and auxiliary tool with respect to the geophysical studies in progress. In particular, a geographical analysis of the phenomenon is proposed here aimed at identifying any spatial dynamics that can be added to the interpretation of seismic activity in a strictly geological and geophysical manner. The research study is focused on the comparison between the historical series of data starting from the year 2005 and those data relating to the last two years 2023 and 2024, in which the phenomenon resumed; particularly, the month of May 2024 is analyzed, which was characterized by high intensity of seismic events in the area. The results obtained through the joint use of spatial analysis tools aim, therefore, to identify any geographical seismic clusters that can then be interpreted in a geophysical way and can be used as an addendum in the current risk maps. Indeed, this geographical approach revealed complex spatial heterogeneities demonstrating the value of combining multiple methodological tools. The findings highlight the importance of multidisciplinary approaches in volcanic research and their critical role in improving hazard assessment and risk mitigation efforts.